PROGRAM PELESTARIAN BAHAN PUSTAKA DI PERPUSTAKAAN IAIN IMAM BONJOL PADANG - Amhar Amhar (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2017)
Abstract: Library material preservation program at the Imam Bonjol IAIN Library. First, the building and its environment, the activities carried out are to periodically check every part of the building and request reports on the physical condition of the building and the environment. Second, make efforts to protect the collection by cleaning dust and dirt, removing stains and masking tape, strengthening library materials by laminating, and providing protection to library materials with protective boxes. Third, create a library preservation program specifically for library staff with educational preservation materials for library materials for strengthening, and librarians / staff. Fourth, implement user education programs (user education) for each prospective user. In the user education program the education of preservation of library materials is intended. Fifth, the collaboration of the Library conducts cooperative relations with parties who can help the implementation of library material preservation programs. Keywords: Preservation program, preservation of library materials, library materialsAbstrak : Program pelestarian bahan pustaka di Perpustakaan IAIN Imam Bonjol Padang meliputi gedung dan lingkungan, koleksi, staf, pemustaka dan kerjasama. Pertama, gedung dan lingkungannya, kegiatan yang dilakukan adalah melakukan pengecekan berkala pada setiap bagian gedung dan membuatnya dalam sebuah laporan kondisi fisik gedung dan lingkungan. Kedua, melakukan usaha perlindungan terhadap koleksi dengan cara membersihkan debu dan kotoran, menghilangkan noda dan selotip, menguatkan bahan pustaka dengan laminating, dan memberikan pelindungan kepada bahan pustaka dengan kotak pelindung. Ketiga, membuat program pelestarian bahan pustaka khusus untuk staf Perpustakaan dengan melakukan pendidikan pelestarian bahan pustaka untuk pimpinan, dan pustakawan/staf. Keempat, melaksanakan program pendidikan pemakai (user education) bagi setiap calon pemustaka. Di dalam program pendidikan pemakai ini dimaksukan pendidikan pelestarian bahan pustaka. Kelima, kerjasama Perpustakaan melakukan hubungan kerjasama dengan pihak-pihak yang dapat membantu terlaksananya program pelestarian bahan pustaka.Kata kunci : Program pelestarian, pelestarian bahan pustaka, bahan pustaka